Literature Review: Lingkungan Sosial dan Perilaku merokok pada Remaja - Devy Riyanti Adii Wijaya; Maya Icha Gayatri; Lina Handayani (Universitas Ahmad Dahlan, 2022)
Smoking behavior is a problem related to public health conditions because it can lead to various health problems. A Global Youth Tobacco study in 2008 showed that the prevalence rate of adolescent smokers in Indonesia was very alarming. This study aims to determine a relationship between the social environment and smoking behavior in adolescents. The research method uses scientific research literature review, by analyzing various articles which valid and relevant to the topic. This study uses the literature of the National Journal published from 2018 to 2021. The database used to collect literature is Google Scholar with the keywords